“Design of a bioreactor for anaerobic digestion” - Fares Khrashi; Odai Hantoly; Ahmad Asad Eshtayeh (My University, 2019)
There is a lot of problems around the world and faces all people around of the world, by having a look for the tremendous scientific development there must be a lot of ways to solve this problem. One of those problems is sewage that effects on people from environmentally and health issues. There were several solutions for this problem, one of those solutions is the device which is designed and manufactured in this project. This device solves the problem of precipitate materials of sewage by using anaerobic digestion and producing useful gases such as methane gas . This device also will be used to run some experiments and use nongaseous products such as compost in agriculture. This project aims to design a small-scale bioreactor, a tank with a size of 8 liters, which will be used for several experimental purposes in Najah national university. In this bioreactor the sludge enters by an external tube, and the bioreactor contains rotating blades that rotate on a certain velocity that increases the growth of bacteria and the activity of the bacteria. The bioreactor also contains a water-jacket where a warm water is used to maintains range of ( ) to the material inside the bioreactor. Therefore, a heating system outside of the bioreactor integrated with a circulating pump is used. This temperature motivates the growth and reproduction of bacteria, also this device is locked so that no oxygen enters on it, a safety valve is also used so it monitors the pressure inside the bioreactor.